Сomplex and protection vibrokontrolyu gas compressor units "visa-pc" - Ясиніцький, Е.П.; Антонов, C.В.; Пустовий, С.О.; Ізбаш, C.В.; Шопяк, О.Б. (Proceedings of National Aviation University (archive), 2006)
Writers wanted to introduce and develop complex “Viza-PC” which meant for dimensioning and reflecting operation vibrofactors, forming the signal for tolerance buildup in system automatic control gascompressor unit.